[Rezension von: Hurtado, Larry W., 1943-, Lord Jesus Christ : devotion to Jesus in Earliest Christianity] - Horbury, William 1942-; Hurtado, Larry W. 1943- (2005)
The ‘devotion’ studied here was central, in the form of cult, in the book to which Hurtado's work since the late 1970s is a sustained response, Wilhelm Bousset's Kyrios Christos (1913, 2nd edn. 1921, English translation 1970). Both scholars explore the history of Christology in the first and second centuries, with special attention to the worship of Christ—rooted by Bousset in hellenistic religion, but by Hurtado in Judaism and primitive Christianity. The learned ardour and imaginative power of Bousset's book, tracing Christusglaube from the beginnings to Irenaeus, gained fresh impetus from the endorsement of many of his positions in the work of Rudolf Bultmann., Hurtado's response first took the form of a book in One God, One Lord (1988, reissued with a substantial new preface in 1998).
Keywords: Rezension